The interaction between law, economics and indigenous cultures: the ocumicho devils - Rojas, Lucero Ibarra (Oñati Socio-Legal Series, 2011)
Seeing cultural rights as the rights that people have to actively involve with and develop their culture and that one important way to do this is by participating of the many art forms in which the cultural identity can be expressed, this research pretends to analyze the role that public policies have in shaping the cultural meaning of indigenous art. Focusing particularly in the indigenous community of Ocumicho in México, in which a long process of interaction with State agencies, tending to the promotion of the art there created, can be observed. This indigenous community was granted the 2009’s Science and Arts National Award in the Popular Arts and Traditions field. With this recognition Ocumicho has become the State held example for the promotion of indigenous art, which makes it only natural to study this same community to understand how State policies impact the expressions of culture. In the relation between State, popular cultures and economics, Ocumicho shows, amongst other things, how State agencies involvement can work towards a mystification of the indigenous, which ignores the complexities and contradictions within their cultures. Such practice has taken the artists to compromising their art to comply with the mystified idea of themselves. The collective right to culture then, when materialized in public policies, seems more restraining than freeing.